OPTIMIZATION OF THE CULTIVATION CONDITIONS OF THE RIBOFLAVIN STRAIN PRODUCER - Radchenko M. M.; Andriiash H. S.; Beiko N. Ye.; Tigunova О. О.; Shulga S. M. (Biotechnologia Acta, 2020)
The aim of the study was to establish the optimal cultivation conditions for increasing accumulation of riboflavin by the producer strain Bacillus subtilis. As an object of the study there were used strains of B. subtilis from “Collection of strains of microorganisms and plant lines for food and agricultural biotechnology” of the State Enterprise “Institute of Food Biotechnology and Genomics of the National Academy of Sciences of Ukraine”. The percentage (10%) and the period of cultivation (16 hours) of the seed material necessary for accumulation of riboflavin were determined. The effect of the carbon source on the accumulation of riboflavin was studied and it was shown that the greatest accumulation (5.2 g/dm3) was with the use of glucose. The dynamics parameters of riboflavin accumulation over time were investigated and the optimal cultivation period was determined (68 hours). The optimal cultivation conditions were selected, which increased the accumulation of riboflavin in the culture fluid (glucose concentration — 120 g/dm3, temperature — 38 oC, and pH of the medium — 7.0) more than twice. It was concluded that the accumulation of riboflavin could be increased by changing the cultivation conditions.